Dynamics of Vibrio ostreicida in Mytilus galloprovincialis through in vivo infections - Leonessi, Martina; Lopez, Jose R.; Cruz-Quintana, Yanis; Auguste, Manon; Andree, Karl B.; Fernandez-Tejedor, Margarita; Vezzulli, Luigi; Furones, Dolors; Canesi, Laura (Frontiers in Immunology, 2025)
IntroductionVibrio species are widespread in coastal environments, where they are being increasingly associated with mortality episodes of farmed bivalves. This is the case for Vibrio ostreicida strain r172 isolated from a mortality event of adult mussels Mytilus galloprovincialis in Spain in 2022.Methods and ResultsIn this study, the infection dynamics and immune responses of adult M. galloprovincialis challenged with V. ostreicida r172 were investigated using different in vivo experimental approaches. First, a virulence assay by injection (1 x 108 CFU/100 µL) was performed at different temperatures (12, 18 and 24 °C). The results showed that mussel mortality (about 50 % within 8 days) was independent of increasing temperatures. Subsequently, an injection/cohabitation experiment was carried out placing together in the same tank V. ostreicida-injected (Donors, 108 CFU/mL) with un-injected mussels (Recipients). The time course of infection was then followed by evaluating positivity to V. ostreicida by PCR, responses of haemolymph components (haemocyte lysosomal membrane stability and serum lysozyme activity) and tissue histopathology (gills and digestive gland). The results showed a partial horizontal transfer of V. ostreicida from infected to uninfected mussels, with transient effects on haemolymph responses and histopathological lesions in both groups. Finally, in order to mimic more realistic environmental conditions, a bath infection experiment was carried out, exposing mussels to V. ostreicida in seawater (105 CFU/mL). This condition resulted in lower stress in haemocytes; moreover, no lysozyme release or histopathological alterations were observed.DiscussionOverall, the results show that M. galloprovincialis is able to cope with challenge with V. ostreicida, indicating that this Vibrio species is moderately pathogenic to adult mussels under the established experimental conditions.